Carbohydrate gel ingestion significantly improves the intermittent endurance capacity, but not sprint performance, of adolescent team games players during a simulated team games protocol - Phillips, S. M.; Turner, A. P.; Sanderson, M. F.; Sproule, J. (European Journal of Applied Physiology, 2012)
The aim of this study was to investigate the influence of ingesting a carbohydrate (CHO) gel on the intermittent endurance capacity and sprint performance of adolescent team games players. Eleven participants [mean age 13.5 ± 0.7 years, height 1.72 ± 0.08 m, body mass (BM) 62.1 ± 9.4 kg] performed two trials separated by 3-7 days. In each trial, they completed four 15 min periods of part A of the Loughborough Intermittent Shuttle Test (LIST), followed by an intermittent run to exhaustion (part B). In the 5 min pre-exercise, participants consumed 0.818 mL/kg BM of a CHO or a non-CHO placebo gel, and a further 0.327 mL/kg BM every 15 min during part A of the LIST (38.0 ± 5.5 g CHO/h in the CHO trial). Intermittent endurance capacity was increased by 21.1% during part B when the CHO gel was ingested (4.6 ± 2.0 vs. 3.8 ± 2.4 min, P < 0.05, r = 0.67), with distance covered in part B significantly greater in the CHO trial (787 ± 319 vs. 669 ± 424 m, P < 0.05, r = 0.57). Gel ingestion did not significantly influence mean 15 m sprint time (P = 0.34), peak sprint time (P = 0.81), or heart rate (P = 0.66). Ingestion of a CHO gel significantly increases the intermittent endurance capacity of adolescent team games players during a simulated team games protocol.